Cranial irradiation induces axon initial segment dysfunction and neuronal injury in the prefrontal cortex and impairs hippocampal coupling. Issue 1 (11th May 2020) - Zhang, Die; Zhou, Wei; Lam, Thanh Thai; Li, Yan; Duman, Joseph G; Dougherty, Patrick M; Grosshans, David R
Abstract: Background: Radiation therapy for brain tumors commonly induces cognitive dysfunction. The prefrontal cortex (PFC) is crucial for a diverse array of cognitive processes, however, its role in radiation-induced cognitive dysfunction is unknown. We previously found that cranial irradiation impairs neuroplasticity along the hippocampal–PFC pathway. Herein, we hypothesized that brain irradiation directly affects the firing properties of PFC neurons, contributing to deficits in neuronal functions. Methods: In vivo recordings were used to monitor the firing activities of PFC neurons and local field potentials in both PFC and hippocampal CA1/subicular regions after cranial irradiation of Sprague Dawley rats. We further assessed the impacts of irradiation on axon initial segments (AISs) with immunofluorescence assays of PFC slices. Results: We found that PFC neurons exhibited increased excitation 3 days after radiation and the timing of increased excitation coincided with elongation of the AIS. At 2 weeks, excitation levels returned to nearly normal levels however the population of spontaneously firing neurons decreased. While the number of NeuN-positive neurons in the PFC was not different, persistent neuronal injury, manifested as ATF-3 staining, was present at 2 weeks. Radiation also disrupted communication along the hippocampal–PFC pathway, with elongation of the phase lag between regions. Analysis of paired-pulse ratios suggested that this was secondary to presynaptic dysfunction. Conclusions: Cranial irradiation excited and injured surviving PFC neurons and was associated with a partial block of PFC's functional coupling to the hippocampus. These deficits in the PFC may contribute to radiation-induced cognitive dysfunction.